Uso de biotecnología modifica salmón para que crezca en la mitad del tiempo convencional - Garro-Monge, Giovanni (Revista Alimentaria. Cámara Costarricense de la Industria Alimentaria. Edición 141, año 2015., 2015)
Transgenic crops of plant origin are widely used globally in animal and male diets, however, no genetically modified animal has been approved for human consumption. This article mentions about the process and the regulated growth of the Atlantic salmon, modified by the company "AquaBounty Technologies". Salmon is one of the products with a demand for exponential growth and the use of technologies to meet this demand remains a safe and innovative alternative for the benefit of public health and the environment.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics; Cultivos transgénicos; Modificación genética; Productos transgénicos; Hormonas; Bioseguridad; Transgenic crops; Genetic modification; Transgenic products; Hormones; Biosecurity